The use and abuse of keystone plant species in restoration practices of terrestrial ecosystems - Ballarin, Caio S.; Amorim, Felipe W.; Watson, David M.; Fontúrbel, Francisco E. (Restoration ecology, 2024)
Keystone plant species are commonly used for restoring degraded terrestrial sites because, despite being encountered in low abundances in natural communities, they interact with multiple species across multiple niche dimensions. Nevertheless, the demographic characteristics of these “great interactors” are often disregarded in restoration planning, which may bring unintended consequences for restoration trajectories once the outcome of species relationships interplays between positive and negative effects depending on the density of interacting species. Therefore, while replanting keystone species at their characteristically low densities may re‐entangle food webs and allow novel plant and animal recruitment, restoring them at high densities can assemble asymmetrical relationships strong enough to affect sympatric plant species establishment, survival, and reproduction. Here, we explore the negative consequences of overusing keystone plant species in sites undergoing restoration and provide specific guidelines for practitioners to maximize the benefits of keystone plants in restoration initiatives.